Bone mineral density as potential individual prognostic biomarker in patients with neurosurgically treated spinal metastasis - H. Asoglu; T. Lampmann; M. Jaber; L. Khalafov; J. Dittmer; I. Ilic; G. H. Gielen; M. Toma; H. Vatter; Z. Bendella; M. Schneider; C. Schmeel; et al. (Journal of Cancer Research and Clinical Oncology)
Abstract Introduction Bone mineral density (BMD) plays a crucial role in diagnosing and treating various systemic chronic diseases. Patients with multiple or singular spinal metastasis (SM) are typically in advanced stages of systemic cancer, often leading to significant alterations in BMD. The present study investigated the prognostic value of perioperative Hounsfield units (HU) as a surrogate independent marker for estimated BMD in patients with SM after surgical treatment (ST). Methods HU values, serving as a surrogate for estimated BMD, were measured from circular regions of interest (ROIs) in the spine -first lumbar vertebra (L1)- from routine preoperative staging computed tomography (CT) scans in 187 patients after ST. The estimated BMD was stratified into pathologic and physiologic values and correlated with survival parameters in our cohorts. Results Median L1 BMD of 92 patients (49%) with pathologic BMD was 79.5 HU (IQR 67.25–93.5) compared to 145 HU (IQR 123–166) for 95 patients (51%) with physiologic BMD (p ≤ 0.001). Patients with pathological BMD exhibited a median overall survival of 8 months compared to 12.2 months in patients with physiologic BMD (p = 0.006). Multivariable analysis revealed pathologic BMD as an independent negative prognostic predictor for increased 1 year mortality (AUC: 0.637, 95% CI: 0.556–0.718; p = 0.001). Conclusions The present study demonstrates that decreased perioperative BMD values, as derived from HU measurements, may represent a previously unrecognized negative prognostic factor in patients of SM after ST. The estimated perioperative BMD could emerge as an individualized, readily available potential biomarker for prognostic, treatment, and discussion of affected patients with SM.